Analisis Perkembangan Sosial Anak Usia Dini Melalui Kegiatan Tari Kelompok - Annisa Zakhra Manullang; Ghina Nabilla; Syanti Laura Berutu; Hilda Zahra Lubis (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study aims to analyze how group dance activities can contribute to the social development of early childhood. Social development in childhood is very important because it is the basis for children's ability to interact, cooperate, and build relationships with their surroundings. The method used in this study is descriptive qualitative with observation, interview, and documentation techniques for children involved in group dance activities at one of the PAUD institutions. The results of the study showed that through group dance activities, children showed improvements in terms of cooperation, communication, empathy, and the ability to follow rules and take turns. These activities also facilitate children in recognizing social roles and building self-confidence. Thus, group dance activities can be used as an effective strategy in supporting the social development of early childhood.